2015
DOI: 10.1038/srep12722
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Characteristics of Doxorubicin Hydrochloride Drug-Doped Salmon DNA Thin Films

Abstract: Double-stranded salmon DNA (SDNA) was doped with doxorubicin hydrochloride drug molecules (DOX) to determine the binding between DOX and SDNA, and DOX optimum doping concentration in SDNA. SDNA thin films were prepared with various concentrations of DOX by drop-casting on oxygen plasma treated glass and quartz substrates. Fourier transform infrared (FTIR) spectroscopy was employed to investigate the binding sites for DOX in SDNA, and electrical and photoluminescence (PL) analyses were used to determine the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…5D) as a function of PEG concentration, the intensities of the peaks increased up to a certain concentration and then began to decrease with further increase in PEG concentration along with that of DOX. In this context, we can conclude that the presence of PEG in the DOX-PEG 500 -epoxy solutions manifests a quenching effect on DOX, depending on PEG concentration, which indicate on the one hand that DOX was bounded to PEG molecule 43 and on the other hand, being also suitable to involve hydrogen bonds with PEG moieties 44 . The emission intensities of DOX-PEG 500 -epoxy, AuPEG 2000 -DOX and iAuPEG 2000 -DOX solutions at higher DOX concentration (around 0.2 mg/mL) are in the same range (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…5D) as a function of PEG concentration, the intensities of the peaks increased up to a certain concentration and then began to decrease with further increase in PEG concentration along with that of DOX. In this context, we can conclude that the presence of PEG in the DOX-PEG 500 -epoxy solutions manifests a quenching effect on DOX, depending on PEG concentration, which indicate on the one hand that DOX was bounded to PEG molecule 43 and on the other hand, being also suitable to involve hydrogen bonds with PEG moieties 44 . The emission intensities of DOX-PEG 500 -epoxy, AuPEG 2000 -DOX and iAuPEG 2000 -DOX solutions at higher DOX concentration (around 0.2 mg/mL) are in the same range (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Since the denaturation process breaks the hydrogen bonds between nucleobases, we focused on how one of the nucleobases, cytosine, would change in its characteristic vibrational peaks for various NaOH concentrations. It is well known that in pristine DNA the cytosine inplane vibration has an absorption peak at ∼1489 cm −1 [31,32], and for the cytosine-guanine bond vibration band it is at ∼1419 cm −1 [31]. It is observed that these two peaks showed significant spectral shifts as the NaOH concentration increased or, equivalently, the relative denaturation increased in the solution precursors.…”
Section: B Ftir Measurement To Confirm Denaturation In Thin Solid Filmmentioning
confidence: 97%
“…Figure 4(a) shows the FTIR absorption spectra of the freestanding solid DNA films with various NaOH concentrations in the solution precursors. The FTIR absorption spectra were divided into three spectral regions: 3600 − 3000 cm −1 for OH stretching, 1800 − 1300 cm −1 for nucleobase vibrations, and 1250 − 700 cm −1 for the sugar and phosphate backbone groups [31]. Since the denaturation process breaks the hydrogen bonds between nucleobases, we focused on how one of the nucleobases, cytosine, would change in its characteristic vibrational peaks for various NaOH concentrations.…”
Section: B Ftir Measurement To Confirm Denaturation In Thin Solid Filmmentioning
confidence: 99%
“…The signicant Raman spectra of DNA nucleotides are categorized into two regions: 400-750 cm À1 for nucleobases and 750-1200 cm À1 for sugar phosphate backbone groups. 21,22 Due to a certain limitation when taking Raman spectra through the synthetic DX tiles-exceeding the Raman signal of the 1Â TAE/ Mg 2+ buffer (40 mM Tris base, 20 mM acetic acid, 1 mM EDTA (pH 8.0), and 12.5 mM magnesium acetate) rather than the signal of the DNA molecules-we alternatively obtained them from the natural DNA duplexes extracted from salmon, which are also valid because the frequency range compared with the simulation is higher than 300 cm À1 . In that relatively high frequency range, the DNA molecule generally shows the local vibrational characteristics of backbones and specic bases.…”
Section: Resultsmentioning
confidence: 99%